A TMS investigation on the role of the cerebellum in pitch and timbre discrimination. Issue 1 (December 2016) - Lega, Carlotta; Vecchi, Tomaso; D'Angelo, Egidio; Cattaneo, Zaira
Abstract Background Growing neuroimaging and clinical evidence suggests that the cerebellum plays a critical role in perception. In the auditory domain, the cerebellum seems to be important in different aspects of music and sound processing. Here we investigated the possible causal role of the cerebellum in two auditory tasks, a pitch discrimination and a timbre discrimination task. Specifically, participants performed a pitch and a timbre discrimination task prior and after receiving offline low frequency transcranical magnetic stimulation (TMS) over their (right) cerebellum. Results Suppressing activity in the right cerebellum by means of inhibitory 1 Hz TMS affected participants' ability to discriminate pitch but not timbre. Conclusion These findings point to a causal role of the cerebellum in at least certain aspects of sound processing and are important in a clinical perspective helping understanding the impact of cerebellar lesions on sensory functions.